Floodplain Modelling by Using HEC-RAS at Sungai Mersing, Johor Malaysia - HASMADI, NURHAZWANI; HAJI ABUSTAN, MUHAMMAD SALLEH (Recent Trends in Civil Engineering and Built Environment, 2022)
: Flood is a common natural problem that occur in Malaysia. This problem will lead to loss of life and property. Johor is one of the states in Malaysia that is frequently hit by floods. Therefore, methods for reducing flood should be applied in purpose of flood controlling. Flood mitigation should be constructed aimed at controlling flooding problems from recurrence. However, before flood mitigation is built, some information is required to predict flooded areas. Several studies have been conducted in developing flood hazard maps. Nevertheless, the nature of the river itself has many complexities and therefore mapping the flooded areas using computers is a simple method besides reducing costs. The main purpose of this study is to produce flood hazard maps and identify rivers that contribute to flood problems. Flood maps are assessed through the area and perimeter. In this research, HEC-RAS software was used to produce flood area maps in Sungai Mersing. Data used is taken from flood history that has occurred in river areas, also included with geometric data as well as river flow data. The geometry data entered includes river topographical data as well as the different Manning roughness coefficient. Final analysis shows areas often exposed to floodplain are on both LOB AND ROB along the river